Biological parameters, life table and thermal requirements of Thaumastocoris peregrinus (Heteroptera: Thaumastocoridae) at different temperatures - Barbosa, L. R.; Santos, F.; Soliman, E. P. [UNESP]; Rodrigues, A. P.; Wilcken, C. F. [UNESP]; Campos, J. M.; Zanuncio, A. J. V.; Zanuncio, J. C. (Nature Publishing Group, 2019)
Temperature affects the development, population dynamics, reproduction and population size of insects. Thaumastocoris peregrinus Carpintero et Dellape (Heteroptera: Thaumastocoridae) is a eucalyptus pest. The objective of this study was to determine biological and life table parameters of T. peregrinus on Eucalyptus benthamii at five temperatures (18 degrees C; 22 degrees C; 25 degrees C; 27 degrees C and 30 degrees C) with a relative humidity (RH) of 70 +/- 10% and photoperiod of 12 hours. The duration of each instar and the longevity of this insect were inversely proportional to the temperature, regardless of sex. The nymph stage of T. peregrinus was 36.4 days at 18 degrees C and 16.1 days at 30 degrees C. The pre-oviposition period was 5.1 days at 30 degrees C and 13.1 days at 18 degrees C and that of oviposition was 7.6 days at 30 degrees C and 51.2 days at 22 degrees C. The generation time (T) of T. peregrinus was 27.11 days at 22 degrees C and 8.22 days at 30 degrees C. Lower temperatures reduced the development and increased the life stage duration of T. peregrinus. Optimum temperatures for T. peregrinus development and reproduction were 18 and 25 degrees C, respectively.